Black Chocolate Consumption Reduces Subjective Symptoms in 18-22 Years Old Females with Premenstrual Syndrome - Nurazizah, Eliza; Tih, Fen; Suwindere, Winny (Maranatha Christian University, 2015)
Menstruation is the release of the endometrium with bleeding every month, except during pregnancy. Before or during menstruation, a woman may experience stiffness or abdominal cramps, mood fluctuations and other physical and psychological disorders, which is termed as premenstrual syndrome (PMS). The aim of this research is to observe and value the effect of dark chocolate on clinical symptoms of PMS. This research is an experimental prospective, using experimental design with one group pre and post test. Subjects were 30 women aged 18-22 years. Every day for 2 weeks before menstruation period, subjects took 20 gram of dark chocolate, then were asked to answer questionaire. The data measured is the score as well as individual PMS symptoms before and after eating dark chocolate, was analyzed using a nonparametric Wilcoxon test, followed by McNemar chi square with Î±=0.05. A highly significant decrease was found in anxiety symptoms, whereas statistically significant reduction was found in fatigue or feeling tired, cramps abdominal, bloating, diarrhea, headache, back pain, change in appetite, muscle or joint pain, and problems in concentration. But the symptom of acne complaint was increased from 73.3% to 76.7%. Consumption of dark chocolate reduces premenstrual syndrome scores on women aged 18-22 years.Â Keywords: dark chocolate, premenstrual syndrome